Association of HLA -A1 and HLA -B8 Antigens with Natural Rubella Infection in Bangladeshi Females (Bangladesh Journal of Medical Microbiology, 2016)
HLA typing was carried out for HLA -A1 and HLA -B8 antigens among 40 Rubella specific immunoglobulin G (RSIgG) positive and 10 RSIgG negative subjects by employing microlympohocytotoxicity technique in viable (>85%) lymphocytes separated from fresh blood. Among these, HLA-A1 antigen was detected in 20 (50%) of RSIgG positive and 4 (40%) of RSIgG negative subjects. The HLA-B8 antigen was detected in 1 (2.5%) of RSIgG positive and in none of the RSIgG negative subjects. None of the subjects had both A1 and B8 antigens. Of the total subjects tested, 24 (48%) were positive for A1 antigen but only 1 (2.0%) was found positive for B8 antigen. In conclusion, HLA -A1 antigen was more frequently found in local population than B8 antigen. However, in this study, a positive correlation of A1 and B8 antigens with natural rubella infection could not be established.Bangladesh J Med Microbiol 2007;01(01):13-16